Type VI Secretion: not just for pathogenesis anymore - Jani, Andrea J. (2010)
Type VI Secretion Systems (T6SS) have been studied primarily in the context of pathogenic bacterial-host interactions. Recent data suggest, however, that these versatile secretion systems may also function to promote commensal or mutualistic relationships between bacteria and eukaryotes, or to mediate cooperative or competitive interactions between bacteria.